Estratégias de enfrentamento da desinformação na pandemia no Brasil e na Argentina : a atuação das agências de Fact-Checking Lupa e Chequeado - Gonçalves, Ana Laura Farias (2021)
The dissertation approaches the strategies adopted by the fact-checking organizations Lupa (Brazil) and Chequeado (Argentina) in the Covid-19 pandemic in 2020. The strategies involve the development of new products, the readjustment of tools already used and changes in the criteria of content selection. The investigation explored the following research problem: “Did the fight against disinformation in the pandemic lead to the development of specific fact-checking strategies by the organizations Lupa (Brazil) and Chequeado (Argentina)?” Among the hypotheses explored, we discovered that the organizations actually made adjustments in their procedures and had their routines modified in the pandemic, adopting different strategies according to the local realities in their countries. The methodological path was based on multiple case studies, following the Yin protocol. The dissertation is composed by three moments: the first chapter focused on normative foundations of journalism necessary to understand the emergence and performance of fact-checking agencies; the second aimed at understanding disinformation as a social phenomenon; and the third analyzing the performance of the two organizations during the Covid-19 pandemic.